2019
DOI: 10.1016/j.applthermaleng.2019.02.134
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic optimization of a packed-bed for utility-scale energy storage

Abstract: The optimization of a packed bed for utility-scale applications is presented in this paper. The effects that particle size, aspect ratio and storage mass have on the roundtrip exergy efficiency of the store are thoroughly analysed. The paper seeks to provide a clear insight of what ranges of values for the aforementioned design parameters are adequate to consider when designing a grid-scale packed bed. Simulations were carried out using a one-dimensional model that accounts for temperature-dependent properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Cárdenas et al 38 investigated that exergy losses are minimized for an aspect ratio between 0.5 and 0.8. Also, it was predicted that the increase in the mass of storage media enhances the storage efficiency of the packed bed.…”
Section: Sensible Energy Storage Technology and Innovationsmentioning
confidence: 99%
“…Cárdenas et al 38 investigated that exergy losses are minimized for an aspect ratio between 0.5 and 0.8. Also, it was predicted that the increase in the mass of storage media enhances the storage efficiency of the packed bed.…”
Section: Sensible Energy Storage Technology and Innovationsmentioning
confidence: 99%
“…Each combination will produce two load profiles ( b and c ) which will be handled by two different packed beds. The design of each packed bed will be optimized for its working load, following the procedure described in Cárdenas et al 26 The optimum signal split is the one that produces the lowest total exergy losses.…”
Section: Examples Of Applicationsmentioning
confidence: 99%
“…Ca´rdenas et al 26 carried out a techno-economic optimization of a utility-scale packed bed. In the study, the authors analyze comprehensively the aforementioned trade-offs.…”
Section: Optimization Of a Packed Bed Thermal Energy Storementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that at least 98% efficiency could be achieved with 30 mm rock diameter and 0.6 m insulation layer. Cardenas et al [4] evaluated packed-bed TES system by developing temperature dependent 1-dimensional 2-phase model. Packed bed with 4 mm rock diameter and 0.6 aspect ratio showed higher efficiency.…”
Section: Introductionmentioning
confidence: 99%